INSTRUMENT FOR DIABETIC FOOT ASSESSMENT: CONSTRUCTION AND VALIDATION - Aguiar da Silva, Beatriz (2022)
To develop a tool to assess the diabetic foot in Primary Health Care in a health unit in the east of Maranhão. This is a methodological study, carried out in the Family Health Strategy (ESF), developed in three stages: 1) Construction based on the literature review; 2) Application of the instrument for the pre-test with the target audience; 3) Application of the content by post-test professionals. In the pre-test phase, 53 patients were identified, the first version of the instrument consisted of 8 items, at the end of the pre-test, the identification items, assessment of risk factors, risk stratification and self-care capacity, the last stage of construction and validation of this instrument was the application by the higher education professionals of the ESF Pirajá. The use of a technology in health services contributes to the adequacy and improvement of the assistance provided.